2003
DOI: 10.1097/01.asn.0000070145.00225.ec
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care for Patients with Chronic Kidney Disease in the United States

Abstract: Abstract. The burden of chronic kidney disease can be assessed by multiple criteria that underscore the need for improved detection, treatment, and outcome monitoring. Several process measures for the care of advanced CKD patients are examined herein. Twenty seven and 11% of patients with CKD in National Health and Nutrition Examination Surveys (NHANES) III had BP Ͻ140/90 and 130/85, respectively. In addition to inadequate prescription of antihypertensive drugs, another confounder is poor diagnostic recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 27 publications
2
59
0
2
Order By: Relevance
“…Our findings support earlier research suggesting that nephrologists treat patients with advanced CKD more appropriately than do non-nephrologists (5,15,(21)(22)(23). However, our analysis demonstrates that there remains an opportunity for improvement in the care of these patients by nephrologists as well.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings support earlier research suggesting that nephrologists treat patients with advanced CKD more appropriately than do non-nephrologists (5,15,(21)(22)(23). However, our analysis demonstrates that there remains an opportunity for improvement in the care of these patients by nephrologists as well.…”
Section: Discussionsupporting
confidence: 88%
“…slowing progression of CKD and development of ESRD (30,31). The quality of pre-ESRD care has been reported to be suboptimal in the United States (32,33), and several key markers of predialysis care in our study indicate differences between the two countries. Norwegian patients with CKD were referred earlier to a nephrologist and had more pre-ESRD visits.…”
Section: Discussionmentioning
confidence: 52%
“…(28) For a patient with CKD in the USA, the outcome was worse than for an equivalent patient with a diagnosis of colon or prostate cancer. (29) It was thought that differences in practice patterns could be responsible for these differences in outcomes. The Third National Health and Nutrition Examination Surveys (NHANES III) in the USA revealed that only 27% of patients with CKD had a blood pressure < 140/90 mmHg, and a majority of patients had severe anaemia (mean haematocrit 27.7%), with only one-quarter being prescribed erythropoietin despite insurance cover being available for most of them.…”
Section: Treating Ckd: Poor Outcomes and Variations In Clinical Practicementioning
confidence: 99%